1997
DOI: 10.1080/01652176.1997.9694738
|View full text |Cite
|
Sign up to set email alerts
|

The effect of discontinuation of postmilking teat disinfection in low somatic cell count herds. I. Incidence of clinical mastitis

Abstract: SUMMARYResults are described of a split-udder trial on the effect of discontinuation of postmilking teat disinfection on the incidence of clinical mastitis in seven dairy herds with a low bulk milk somatic cell count and a high incidence of clinical mastitis. Overall incidence of clinical mastitis was non-significantly lower (18%), whereas the incidence of the most prevalent pathogen associated with clinical mastitis, Escherichia coli, was significantly lower in quarters for which postmilking teat disinfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
1
9
0
5
Order By: Relevance
“…To combat mastitis, sophisticated models, such as the five-point-plan, have been adopted worldwide and have resulted in significant reduction of subclinical mastitis. However, despite classical efforts for control and prevention, the susceptibility of cows to coliform infection is increasing [131,205,224]. Moreover, from both epidemiological and experimental studies it can be concluded that severity of coliform mastitis is of much more concern than its incidence.…”
Section: Clinical Severity Classificationmentioning
confidence: 99%
“…To combat mastitis, sophisticated models, such as the five-point-plan, have been adopted worldwide and have resulted in significant reduction of subclinical mastitis. However, despite classical efforts for control and prevention, the susceptibility of cows to coliform infection is increasing [131,205,224]. Moreover, from both epidemiological and experimental studies it can be concluded that severity of coliform mastitis is of much more concern than its incidence.…”
Section: Clinical Severity Classificationmentioning
confidence: 99%
“…There was no cure of already infected quarters (Parker et al, 2008). However, both Schukken et al (1991) and Lam et al (1997) identified an association between the use of iodine PMTD and more clinical coliform mastitis. These are both field studies, however Schukken et al's (1991) study were not based on randomisation of herds and could thus have a selection bias.…”
Section: Discussionmentioning
confidence: 83%
“…We have extended the modelling of Lam et al [7,8,[18][19][20], on the transmission of mastitis pathogens as well as providing some validation of a standard multispecies model structure [6]. The model also permits an explanation for the drop in basic reproduction number reported by Lam et al [7].…”
Section: Discussionmentioning
confidence: 91%
“…Barkema et al [21] observed that approximately 60 % of Dutch dairy farms were practicing postmilking teat disinfection. Evidence already exists that casts doubt on the efficacy of postmilking teat disinfection in the prevention of Escherichia coli (a colifom, major pathogen) [20]. Infections with Escherichia coli usually originate from the environment and are not prevented by teat disinfection.…”
Section: Discussionmentioning
confidence: 99%